PERFORMANCE STUDY OF OVERVOLTAGE CUTTING BY LIGHTNING ARRESTER DUE TO LIGHTNING INDUCTION - Kurniawan Ali Male; Lanto Mohamad Kamil Amali; Yasin Mohamd; Nova Elysia Ntobuo (Universitas Tarumanagara, 2025)
Lightning disturbances often cause induced overvoltages on 20 kV medium voltage distribution overhead lines, which can shorten equipment life and trigger power outages. This study aims to evaluate the cutting performance of two types of lightning arresters made of ceramic and polymer in reducing lightning-induced voltage surges through high-voltage impulse testing in the laboratory. The tests replicated standard impulse waves and were conducted in stages at 20 kV, 30 kV, 40 kV, and 50 kV levels, with each level repeated several times for data reliability. The main parameters analyzed included the measured peak voltage, response time (μs), and the cutting percentage compared to unprotected conditions, based on validated oscilloscope readings (time/div and volt/div). The results showed that both arresters reduced the induced voltage in most test scenarios, with the highest effectiveness occurring at 30 kV impulses. Quantitatively, ceramic arresters achieve a cutoff of 0.39–4.17 V (2.27–22.3%), while polymer arresters achieve 1.46–4.67 V (8.44–24.97%), and at 20 kV no significant cutoff is observed. In general, the performance of polymer lighting arresters is better than ceramic lighting arresters, which indicates the ability of polymer materials and housing designs to maintain lower residual voltages when facing fast transients Abstrak Gangguan petir seringkali menimbulkan tegangan lebih terinduksi pada saluran udara distribusi tegangan menengah 20 kV yang berakibat memperpendek umur peralatan dan memicu pemadaman listrik. Penelitian ini bertujuan mengevaluasi kinerja pemotongan dua tipe lightning arrester berbahan keramik dan berbahan polimer dalam mereduksi lonjakan tegangan akibat induksi petir melalui pengujian impuls tegangan tinggi di laboratorium. Pengujian mereplikasi gelombang impuls standar dan dilakukan bertingkat pada level 20 kV, 30 kV, 40 kV, dan 50 kV dimana setiap level diulang beberapa kali untuk reliabilitas data. Parameter utama yang dianalisis meliputi tegangan puncak terukur, respons waktu (μs), serta persentase pemotongan terhadap kondisi tanpa proteksi, berdasarkan pembacaan osiloskop yang telah divalidasi (time/div dan volt/div). Hasil menunjukkan kedua arrester menurunkan tegangan induksi pada sebagian besar skenario uji, dengan efektivitas tertinggi muncul pada impuls 30 kV. Secara kuantitatif, arrester keramik mencapai pemotongan 0,39–4,17 V (2,27–22,3%), sedangkan arrester polimer 1,46–4,67 V (8,44–24,97%) dan pada tegangan 20 kV tidak teramati pemotongan berarti. Secara umum kinerja lighting arrester polimer lebih baik dibandingkan lighting arrester berbahan keramik, yang mengindikasikan kemampuan material dan rancangan housing polimer untuk menjaga tegangan residual lebih rendah saat menghadapi transien cepat